Marketing Islam Through Zakat Institutions in Indonesia - Asep Saepudin Jahar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
This essay examines the transformation of charity administration operated by zakat agencies in Indonesia with special reference to Dompet Dhu’afa. This study offers an approach of marketing Islam in elaborating on zakat organizations that exercise community development through economic, social and humanitarian aid for disadvantaged people. The practice of zakat administration is basically designed to develop community-based programs among the poor and not struggle for Islamization or the politicization of Islam. Marketing zakat agencies does not attempt to commercialize religion; rather it is committed to the objective advancement about the effectiveness of religious teachings in Muslim communities. Marketing zakat to the public tries to demonstrate its role as the vanguard of social justice especially for the benefit of the destitute and needy. The proliferation of state-sponsored zakat agencies (BAZNAS) vis-à-vis community-based zakat organization (LAZ) is not a case of state-initiated Islamization. It is rather an attempt at regulating public affairs, including zakat funds, within the state administration.DOI: 10.15408/sdi.v22i3.2353